Management performance of medium level managers at the UCLA, Barquisimeto. Venezuela (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
The following is a descriptive research in the mode of field design, with the purpose of measuring the management performance of medium level managers (Faculty Directors) of the different Faculties, at the U.C.L.A. Barquisimeto – Venezuela, as from the analysis of two variables: Functions and Manager Roles. This research is made on a sample population of 16 subjects, made up by thirteen (13) directors of programs and three (3) coordinators of new careers. In order to obtain reliable results an adaptation of evaluation 360ª is applied, thus avoiding not only to accept the information provided by the subject of study, but also obtaining information from people interacting with him: Superiors (Deans) and Professors. In order to collect data, three instruments where used (questionnaires) with open and closed questions, headed to Faculty Directors, his superiors and his subordinated, which were applied by the investigator through an interview and direct observation. The results were that medium level managers at the U.C.L.A. show a high compliance of their management functions, planning, organization, direction and control; showing also strengths in their performance but some weaknesses in matters as: technical level of the process of planning and motivation, leadership stimulation and level of participation. It is also a conclusion that roles such as Interpersonal, of Information, and of Decision are performed to a high level; however, roles such as Interpersonal and of Information are outstanding. Also some weaknesses in roles of leadership and resource assignment were found.
Keywords: management; performance; functions; roles; medium level management